(untitled) (International Journal of Engineering and Computer Science, 2018)
There has been a rapid increase in the use of information and communication technologies (ICTs) as teaching and learning tools in education. Electronic learning (E-learning) is fast becoming one of the most popular learning environments in the field of education in most universities globally, including in Saudi Arabia. The use of e-learning is now gaining common and popular approval, due to the fact that, as well as reducing classroom time it also creates its own impact on the stakeholders. The use of E-learning in the realm of education is a paradigm shift from traditional practice, brought about by technological development, such as the Internet and digital programmer-enabled mobile apps. In addition, faculty members at many higher education institutions in the KSA are facing challenge in regards to the implementation of E-learning in their teaching. Hence, this paper will investigate the impact of use E-learning and ICT in the university level. A quantitative data approach was used with the analysis of 375 questionnaires. Validity and reliability of the questionnaire were checked and statistical treatments such as percentages, means, frequencies, standard deviation and analysis of variance (ANOVA) were conducted. The results from the quantitative data analysis identified statistically significant difference in favour of those who are holders of Ph.D. Degrees. Also, identified statistically significant difference in favour of those with between (15-24) years’ experience.